2016
DOI: 10.1155/2016/7827140
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Complication of Herpes Zoster: Segmental Zoster Paresis

Abstract: Herpes zoster is a common presentation in both the community and emergency department; however segmental zoster paresis is a rare complication that can lead to misdiagnosis. We present a case of a 74-year-old Indian gentleman with a background of well controlled diabetes mellitus, hypertension, and ischaemic heart disease who presented with sudden right lower limb weakness. This was preceded by a 5-day history of paraesthesia starting in the right foot and ascending up the right lower limb. On examination, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Motor recovery varied from full recovery within a few days to partial recovery after 2 years. [1,3,1416] Our patient did not gain full recovery, even after 6 months. This is thought to be due to the degree of motor nerve involvement.…”
Section: Discussionmentioning
confidence: 60%
“…Motor recovery varied from full recovery within a few days to partial recovery after 2 years. [1,3,1416] Our patient did not gain full recovery, even after 6 months. This is thought to be due to the degree of motor nerve involvement.…”
Section: Discussionmentioning
confidence: 60%
“…We raise a hypothesis to explain the occurrence of cranial motor neuropathy in herpes zoster infection. The reactivation of latent VZV in the cranial sensory ganglia (geniculate ganglion and/or trigeminal ganglion) may activate cellular immune responses and induce collateral damage to nearby single or multiple cranial motor nerves due to a close proximity of the cranial motor nerves and sensory ganglia [21].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of C3-C5 motor nerves could lead to diaphragmatic paresis and induce the clinical manifestations, including dyspnea and pulmonary dysfunction (42,43). The affected ganglion segments and possible clinical manifestation are summarized in Table 1 (3,7,28,34,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Clinical Characteristics Of Szpmentioning
confidence: 99%
“…Previous studies have reported that the infection of VZV accounts for 0.5% -5% of all the motor impairments (3). Nevertheless, the exact odds related to this complication still remain unclear, which is mainly due to the following 2 factors: 1) the difficulties in clinical diagnosis (the differentiation from myasthenia induced by other causes, or the limb weakness masked by drastic pain); and 2) atypical clinical symptoms of segmental intercostal paresis and abdominal muscle paresis.…”
mentioning
confidence: 99%